Virtue epistemology and confucian philosophy - MI, Chienkuo (Institutional Knowledge at Singapore Management University, 2018)
This chapter focuses on the epistemic significance of Confucian ideas, rather than the ideas of Chinese philosophy more generally. It describes how Confucian philosophy has traditionally been seen by scholars of Chinese philosophy. The chapter introduces the reader to epistemologically significant Confucian ideas. Within the field of virtue epistemology there are two basic strands, virtue reliabilism and virtue responsibilism. Both have roots in Aristotelian philosophy and have been revived and developed within post-Gettier epistemology. Virtue responsibilists often list and discuss intellectual virtues such as: open-mindedness, conscientiousness, intellectual honesty, fair-mindedness, and inquisitiveness. Virtue responsibilists have tended to focus on the analysis of individual intellectual virtues. The chapter concludes by briefly setting out how our account of skillful reflection, an example of an account informed by Confucian thought, bridges the divide between virtue reliabilism and virtue responsibilism.